Application of Taguchi's methods to investigate factors affecting emissions of a diesel engine running with tobacco oil seed methyl ester. (1st January 2012) - Parlak, Adnan; Karabaş, Hülya; Özsert, İbrahim and Ayhan, Vezir and Cesur, İdris
Different kinds of vegetable oils and their methyl/ethyl esters have been tested in diesel engines. However, studies reporting the effects of tobacco seed oil and Tobacco Seed Oil Methyl Ester (TSOME) on emissions of diesel engines are limited. One of the most important issues is to investigate parameters that affect the yield of biodiesel and their interactions on emissions of a diesel engine. The Taguchi method is a useful tool for this purpose. Two different catalysts (KOH and NaOH), four different blends (B10, B20, B50 and B100) and four engine speeds were used during full-load tests. Optimal catalyst type, engine speed and TSOME blends on exhaust emissions were determined using Taguchi's technique. The Taguchi design method revealed that choosing right catalyst and the blend rate are important two factors in view of minimisation of pollutant emissions.